Auditing of Energy Use and Costs Analysis in the Algerian Agro Food Sector: A Case Study in Three Dairies, ISSN/ISBN 0199-8595/1546-0118 - Boutagriout Badreddine; Hamouda Chaâbane; Smadi Hacene (JAEE Journal of the Association of Energy Engineering Auditing of Energy Use and Costs Analysis in the Algerian, 2015)
The industrial sector accounts for almost one fourth of the final energy consumption in Algeria. An energy survey was carried out in three Algerian dairies, and the energy use and cost analysis is presented in this article. Electricity and natural gas are the main resources that are used in the dairy industry. The specific energy consumption related to electricity and natural gas was found to be in the ranges of 0.03–0.08 kWh/kg and 0.10-0.22 kWh/kg respectively. Also, a relationship of energy consumption, energy costs and production is presented and the findings could be used to establish an energy management system aimed at using energy more efficiently. Finally, this paper calls for more investigations of other industries to obtain reliable indicators.